2022
DOI: 10.3389/fimmu.2022.941530
|View full text |Cite|
|
Sign up to set email alerts
|

Potential Gut Microbiota Features for Non-Invasive Detection of Schistosomiasis

Abstract: The gut microbiota has been identified as a predictive biomarker for various diseases. However, few studies focused on the diagnostic accuracy of gut microbiota derived-signature for predicting hepatic injuries in schistosomiasis. Here, we characterized the gut microbiomes from 94 human and mouse stool samples using 16S rRNA gene sequencing. The diversity and composition of gut microbiomes in Schistosoma japonicum infection-induced disease changed significantly. Gut microbes, such as Bacteroides, Blautia, Ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Finally, Parabacteroides , Prevotella , and Butyrivibrio were associated with salmonellosis, EPEC, and helminth infections. Of note, similar observations have been reported previously, both from epidemiological assessments and experimental veterinary medical assessments [ 61 , 62 , 63 , 64 , 65 ]. Such coincidences in the literature confirm the findings of the assessments presented here, although potential causal relations are still largely unknown.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, Parabacteroides , Prevotella , and Butyrivibrio were associated with salmonellosis, EPEC, and helminth infections. Of note, similar observations have been reported previously, both from epidemiological assessments and experimental veterinary medical assessments [ 61 , 62 , 63 , 64 , 65 ]. Such coincidences in the literature confirm the findings of the assessments presented here, although potential causal relations are still largely unknown.…”
Section: Discussionsupporting
confidence: 87%
“…Hence, more findings clarifying the directionality of these associations is needed. In addition, recent experimental data suggest that, in the future, analysis of the microbiota could predict the outcomes of some helminth infections such as schistosomiasis [ 116 ]. Moreover, oncoming data from experimental research would help increase our understanding of the mechanisms of the helminth–microbiota interactions, including studies that elucidate the involved host’s genetic factors.…”
Section: Perspectivesmentioning
confidence: 99%
“…The dysbiosis of intestinal bacteria is the common finding in schistosomiasis. Evidence has shown that the disturbance of bacterial diversity in intestine occurred with Schistosoma infection with, both sex [ 35 ], single sex [ 36 ], and S . haematobium that the adults do not release their eggs to intestinal lumen [ 37 ].…”
Section: Discussionmentioning
confidence: 99%